2017
DOI: 10.5116/ijme.5a10.04e1
|View full text |Cite
|
Sign up to set email alerts
|

Predictive validity of pre-admission assessments on medical student performance

Abstract: ObjectivesTo examine the predictive validity of pre-admission variables on students’ performance in a medical school in Saudi Arabia. MethodsIn this retrospective study, we collected admission and college performance data for 737 students in preclinical and clinical years. Data included high school scores and other standardized test scores, such as those of the National Achievement Test and the General Aptitude Test. Additionally, we included the scores of the Test of English as a Foreign Language (TOEFL) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 31 publications
2
18
0
Order By: Relevance
“…More weight should therefore be assigned to it. This result matches those of other national studies conducted in KSA (e.g., [11], [12], [15], [16]), which also show that SAAT score is the most significant positive predictor of student performance in Saudi medical schools. However, our result contradicts what is proposed in another national study [14], which found that the HSGA affects student CGPA more than the other two criteria.…”
Section: ) Evaluation Metricssupporting
confidence: 90%
“…More weight should therefore be assigned to it. This result matches those of other national studies conducted in KSA (e.g., [11], [12], [15], [16]), which also show that SAAT score is the most significant positive predictor of student performance in Saudi medical schools. However, our result contradicts what is proposed in another national study [14], which found that the HSGA affects student CGPA more than the other two criteria.…”
Section: ) Evaluation Metricssupporting
confidence: 90%
“…However the study was done on a very small sample of 91 students. In a bigger study on 737 students the SAAT but not GAT was a positive predictors of cGPA but only in the pre-clinical years and not clinical years (6).…”
Section: Discussionmentioning
confidence: 79%
“…Dabaliz et al 25 showed that performance in the PT in the preclinical stages of a medical course was not predicted by five variables of the admissions test. 25 In our single dependency study, no correlation between marks in the UAT and in the PT performed at the end of the medical course was observed. However, similarly to OSCE, PT scores helped to increase the correlation between the variables when multivariate analysis was performed.…”
Section: Discussionmentioning
confidence: 99%
“…15 Little is known about the association between marks in admissions tests and in the PT at the end of a medical course. Dabaliz et al 25 showed that performance in the PT in the preclinical stages of a medical course was not predicted by five variables of the admissions test. 25 In our single dependency study, no correlation between marks in the UAT and in the PT performed at the end of the medical course was observed.…”
Section: Discussionmentioning
confidence: 99%